Analysis of Synapses in Cerebral Organoids. Issue 9 (September 2019) - Yakoub, Abraam M.; Sadek, Mark
Cerebral organoids are an emerging cutting-edge technology to model human brain development and neurodevelopmental disorders, for which mouse models exhibit significant limitations. In the human brain, synaptic connections define neural circuits, and synaptic deficits account for various neurodevelopmental disorders. Thus, harnessing the full power of cerebral organoids for human brain modeling requires the ability to visualize and analyze synapses in cerebral organoids. Previously, we devised an optimized method to generate human cerebral organoids, and showed that optimal organoids express mature-neuron markers, including synaptic proteins and neurotransmitter receptors and transporters. Here, we give evidence for synaptogenesis in cerebral organoids, via microscopical visualization of synapses. We also describe multiple approaches to quantitatively analyze synapses in cerebral organoids. Collectively, our work provides sufficient evidence for the possibility of modeling synaptogenesis and synaptic disorders in cerebral organoids, and may help advance the use of cerebral organoids in molecular neuroscience and studies of neurodevelopmental disorders such as autism.